Psychometric properties of the Brazilian Portuguese version of the Obsessive-Compulsive Inventory: Revised (OCI-R) Propriedades psicométricas da versão em português do Brasil da Obsessive-Compulsive Inventory: Revised (OCI-R) - Fernanda P. Souza; Edna B. Foa; Elisabeth Meyer; Kátia G. Niederauer; Aristides V. Cordioli (Revista Brasileira de Psiquiatria, 2011)
OBJECTIVE: The present study was designed to evaluate the psychometric properties of the Brazilian Portuguese version of the Obsessive-Compulsive Inventory - Revised. METHOD: The Obsessive-Compulsive Inventory - Revised was administered toa total of 260 participants: a clinical sample of 130 patients with anxiety disorders (64 with a diagnosis of obsessive-compulsive disorder patients, 33 diagnosed with social phobia, and 33 with panic disorder) and a sample of 130 non-clinical subjects. RESULTS: The findings indicate that the Obsessive-Compulsive Inventory - Revised is a valid measure for identifying and assessing the severity of the six symptom subtypes in obsessive-compulsive disorder.The original factor structure of the instrument was replicated in an exploratory factor analysis. Test-retest reliability was examined using data from 64 obsessive-compulsive disorder patients who completed the inventory on two different occasions. In each sample, the overall and subscale scores showed moderate to good internal consistency, good convergent and divergent validity, and sensitivity to changes resulting from cognitive-behavioral group therapy changes. CONCLUSION: Our findings indicate that the Brazilian Portuguese version of the Obsessive-Compulsive Inventory - Revised retains the psychometric properties of its original version and the Spanish, German and Iceland versions. OBJETIVO: O presente estudo foi delineado para avaliar as propriedades psicométricas da versão em português do Brasil do Obsessive-Compulsive Inventory - Revised. MÉTODO: O Obsessive-Compulsive Inventory - Revised foi aplicado em um total de 260 indivíduos: em uma amostra clínica de 130 pacientes (64 pacientes com transtorno obsessivo-compulsivo, 33 pacientes com fobia social e 33 pacientes com transtorno do pânico) mais uma amostra não clínica de 130 sujeitos. RESULTADOS: Os resultados indicam que o Obsessive-Compulsive Inventory - Revised é uma medida válida para identificar e avaliar a severidade dos seis subtipos de sintomas do transtorno ...